1990
DOI: 10.1093/mutage/5.5.475
|View full text |Cite
|
Sign up to set email alerts
|

Paracetamol inhibits replicative DNA synthesis and induces sister chromatid exchange and chromosomal aberrations by inhibition of ribonucleotide reductase

Abstract: Effects of paracetamol have been studied in a hydroxyurea (HU)-resistant mouse mammary tumour cell line TA3H2, shown to overproduce the small subunit of ribonucleotide reductase. These TA3H2 cells were much more resistant than the TA3H (wild-type) cells towards the inhibitory effect of paracetamol on cell growth, IC50 0.55 mM paracetamol for the wild-type compared to 2.7 mM for the HU-resistant cells. The reduced cell growth was due to an inhibition of replicative DNA synthesis, judged from an increased percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 0 publications
2
24
1
Order By: Relevance
“…The drug directly inhibits ribonucleotide reductase, which reduces cell growth by stopping DNA replication (25). Then, the relative number of cells in the S phase increases (25), as we observed after exposure of mIMCD3 cells to APAF (Figs.…”
Section: Discussion Nsaids and Caffeine Are Directly Toxic To Imcd Cementioning
confidence: 61%
“…The drug directly inhibits ribonucleotide reductase, which reduces cell growth by stopping DNA replication (25). Then, the relative number of cells in the S phase increases (25), as we observed after exposure of mIMCD3 cells to APAF (Figs.…”
Section: Discussion Nsaids and Caffeine Are Directly Toxic To Imcd Cementioning
confidence: 61%
“…However, APAP, has an additional toxic effect that may be more pertinent to the toxicity that we observe. The drug directly inhibits ribonucleotide reductase, which reduces cell growth by stopping DNA replication (Hongslo et al, 1990). Then, the relative number of cells in S phase increases (Hongslo et al, 1990), as we observed following exposure of mIMCD3 cells to APAP (Rocha et al, 2001).…”
Section: Discussionmentioning
confidence: 70%
“…Treating mice with increasing doses of APAP for 8 days increases hepatocellular proliferation 4-fold (Shayiq et al, 1999). Reports of decreased proliferation include that APAP produces cell cycle block in Hepa 1-6 cells (Boulares et al, 1999) and HL-60 cells (Wiger et al, 1997), reduces replicative DNA synthesis in mouse mammary tumor cells (Hongslo et al, 1990), and reduces proliferation of HepG2 cells (Dai and Cederbaum, 1995) It has not been clear what factors deter- mine whether APAP will increase or decrease the cell number, but the rate of proliferation and DNA replication apparently is important in p1rIMCD cells. It would be of interest to know whether high levels of APAP increase the otherwise slow rate of proliferation of renal inner medullary cells in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genotoxic action of paracetamol in somatic cells has already been reported for mice bone marrow as chromosomal aberrations (CA) and sister chromatid exchange (SCE) (Giri et al, 1992). Treatment with paracetamol also induced SCE and CA and inhibits replicative DNA synthesis in mouse mammary tumor cell line (Hongslo et al, 1990). The significant increase in CA induced by paracetamol may be attributed to the fact that paracetamol can induce genotoxicity through DNA damage.…”
Section: Discussionmentioning
confidence: 98%